Interpreting Gesture as Motive: A Transformational Perspective on Replication in R. Murray Schafer’s Seventh String Quartet - Lind, Stephanie (Intersections, 2008)
AbstractWhile the text, instrumentation, and performance details of Schafer’s Seventh String Quartet (which include an obligato soprano, colour and costume motifs, and texts based on the writings of a schizophrenic woman) seem to distract from the work’s pitch structure, seemingly disparate motives can instead be considered closely related because they repeat a particular transpositional gesture. This article uses transformational network analysis, a recently developed theoretical approach incorporating elements of mathematical and musical set theory, to illustrate similarities between these pitch motives. A brief introduction to transformational network analysis is included for those not familiar with its terminology.